2022
DOI: 10.1109/jstars.2022.3204223
|View full text |Cite
|
Sign up to set email alerts
|

New Generation Hyperspectral Data From DESIS Compared to High Spatial Resolution PlanetScope Data for Crop Type Classification

Abstract: Thoroughly investigating the characteristics of new generation hyperspectral and high spatial resolution spaceborne sensors will advance the study of agricultural crops. Therefore, we compared the performances of hyperspectral Deutsches Zentrum fur Luft -und Raumfahrt-(DLR) Earth Sensing Imaging Spectrometer (DESIS) and high spatial resolution PlanetScope in classifying eight crop types in California's Central Valley during the 2020 growing season. The DESIS sensor onboard the International Space Station colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 105 publications
(134 reference statements)
0
2
0
Order By: Relevance
“…The spatial resolution is approximately 30 m at the pixel scale. A study by Aneece et al [ 250 ] compared agricultural image classification data from the Central Valley, California in 2020, between DESIS 30 m (hyperspectral) and PlanetScope’s Dove-R (4-band) 3–4 m high-spatial-resolution data. This one-on-one comparison between hyperspectral DESIS vs. high-spatial-resolution Dove data revealed that the hyperspectral images outperformed the high-spatial-resolution data.…”
Section: The International Space Station (Iss) Hosts Experimental Ins...mentioning
confidence: 99%
“…The spatial resolution is approximately 30 m at the pixel scale. A study by Aneece et al [ 250 ] compared agricultural image classification data from the Central Valley, California in 2020, between DESIS 30 m (hyperspectral) and PlanetScope’s Dove-R (4-band) 3–4 m high-spatial-resolution data. This one-on-one comparison between hyperspectral DESIS vs. high-spatial-resolution Dove data revealed that the hyperspectral images outperformed the high-spatial-resolution data.…”
Section: The International Space Station (Iss) Hosts Experimental Ins...mentioning
confidence: 99%
“…Using satellite imagery [35,36,37,38], aerial photography [39,40,41,42], and drones, remote sensing and image-based models collect spatial and temporal information about crop growth levels. These models [43,44,45] estimate crop yield using techniques such as vegetation indices, image classification, and object detection process.…”
Section: Models Based On Processmentioning
confidence: 99%